2015
DOI: 10.1097/pcc.0000000000000337
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Disposition Following Telemedicine Consultations in Rural Emergency Departments

Abstract: Although the overall admission rate among patients receiving telemedicine consultations was lower than that among patients receiving telephone consultations, there were no statistically significant differences between the observed-to-expected admission ratios using Pediatric Risk of Admission II and Revised Pediatric Emergency Assessment Tool. Our findings may be reassuring in the context of previous research, suggesting that telemedicine specialty consultations can aid in the delivery of more appropriate, saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 27 publications
1
46
1
Order By: Relevance
“…Without detailed information on the therapies and interventions performed in the EDs as a result of the telemedicine consultations, we are unable to directly attribute the lower PRISM III scores on arrival to the PICU to the telemedicine program. However, our claim finds support in prior research showing that pediatric critical care telemedicine programs in EDs were effective in lowering transfer rates of children to facilities providing higher levels of care (21). Fourth, we considered the intervention in this study to be the telemedicine program and not the specific consultation modality-so not all patients transferred from EDs with telemedicine received a telemedicine consultation.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Without detailed information on the therapies and interventions performed in the EDs as a result of the telemedicine consultations, we are unable to directly attribute the lower PRISM III scores on arrival to the PICU to the telemedicine program. However, our claim finds support in prior research showing that pediatric critical care telemedicine programs in EDs were effective in lowering transfer rates of children to facilities providing higher levels of care (21). Fourth, we considered the intervention in this study to be the telemedicine program and not the specific consultation modality-so not all patients transferred from EDs with telemedicine received a telemedicine consultation.…”
Section: Discussionmentioning
confidence: 57%
“…of telemedicine to support the care of seriously ill children in referring EDs results in higher provider and patient satisfaction (16)(17)(18)(19), improved clinical outcomes (20), fewer medication errors (12), and higher quality of medical care (17,21). Pediatric telemedicine consultations can sometimes obviate unnecessary transfers (20)(21)(22)(23), facilitate timely and appropriate stabilization prior to and during the transfer process (22,23), and may result in lower severity of illness at admission to the PICU and improved outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have cited criticisms of community emergency care to advocate more strongly for routine emergency pediatric telemedicine usage . While this may be very appropriate to improve care for the critically ill and for certain other conditions, our findings suggest that simpler, less costly alternatives may effectively address some overtransfers without unnecessary consultation or supervision. While sufficient, real‐time video telemedicine may not be necessary to accurately risk stratify seizure, fracture, or traumatic brain injury patients, while it may improve transfer performance for children with respiratory infections or wheezing.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, in a separate analysis of different emergency departments participating in this telemedicine network, researchers found that the frequency of medication errors was significantly lower (3.4%) than the rate of medication errors among children receiving telephone consultations (10.8%) and when no consultations were obtained (12.5%) (73). Finally, when the appropriateness of interfacility transfers were evaluated using previously validated pediatric emergency medicine prediction models, researchers found that the use of telemedicine resulted in more appropriate rates of admissions, specifically reducing the frequency of admission for children who could be managed in an ambulatory or local hospital setting (74).…”
Section: Emergency Departmentmentioning
confidence: 99%